PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG LISTING DI BURSA EFEK INDONESIA - Ryan Anugrah Pratiwi; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of good corporate governance and firm size on firm value on food and beverage companies listed in Indonesia Stock Exchange (IDX). The ratio of good corporate governance that is used as the independent variable is managerial ownership, institutional ownership, board of directors, independent board and audit committee. The ratio of the size of the company is used as the independent variable is the natural logarithm of total assets (Ln Total asset). While used as the dependent variable was measured with the company's price-book value (PBV) listed on the Indonesia Stock Exchange (IDX). The method used to observe the effect of good corporate governance and company size on the value of the company is by using multiple linear regression. The data used in this research is secondary data, financial statements and annual report annual report. The data listed in the Indonesia Stock Exchange (IDX) for 5 years from the period 2010 to 2014. Sampling was done by purposive sampling, used was 6 companies. Data analysis using multiple linear regression analysis, t-test, f and the coefficient of determination test. Data analysis using multiple linear regression analysis with SPSS 21. The analysis showed that the variable good corporate governance influence significantly affect the value of food and beverage companies listed in Indonesia Stock Exchange. While the variable size of the company does not significantly affect the value of food and beverage companies listed in Indonesia Stock Exchange. Simultaneous research results showed no significant effect of the variable good corporate governance and company size on the value of food and beverage companies listed in Indonesia Stock Exchange (IDX).Keywords : good corporate governance, firm size, the value of the company